Phototreatment of Palm Oil Mill Effluent (POME) over Cu/TiO2 Photocatalyst - Kim Hoong Ng; Mohd. Rizauddin Deraman; Chun How Ang; Soo Kee Chong; Zi Ying Kong; Maksudur R. Khan; Chin Kui Cheng (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The current work reported on the use of different formulations of Cu/TiO2 photocatalysts for the UV-irradiation of palm oil mills effluent (POME). Different copper loadings, viz. 2 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt% and 25 wt% were doped onto titania. XRD pattern confirmed the presence of anatase TiO2 as primary phase due to mild calcination temperature (573 K). Photo-decomposition of POME over 20 wt% Cu/TiO2 exhibited the highest conversion (27.0%) attributed to its large pore diameter (20.0 nm). In addition, optimum loading was 0.83 g/l. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)